In vitro Evaluation of Antioxidant Capacity of Algerian Propolis by Spectrophotometrical and Electrochemical Assays - Rebiai, A; Lanez, T; Belfar, ML (Asian Network for Scientific Information, 2011)
The aim of the present study was to evaluate the antioxidant capacity and the total phenolic content of propolis extract, obtained from colonies of honeybees located in El-Oued (south of Algeria). The total phenolic content was evaluated using the Folin-Ciocalteu method and the anticoxidant capacity was measured using the following methods: 2, 2-diphenyl-1-picryhydrazyl free radical scavenging capacity and reducing power capacity for spectrophotometrical techniques, ascorbic and gallic acids equivalent antioxidant capacity assays for electrochemical techniques. Both techniques allowed an evaluation of the antioxidant capacity of methanolic propolis extract. The electrochemical techniques were performed by cyclic voltammetry, the results suggest that propolis extract do not reveal similar electrochemical responses to that of ascorbic and gallic acids, suggesting a different electroactive chemical composition and oxidation potential more positive than that of the standard (ascorbic acid), however this does not suggest that propolis has a lower antioxidant capacity. The results suggest also that propolis extract possess antioxidant capacity in vitro conditions.
Article
Keywords: Propolis, antioxidant capacity, honeybee, cyclic voltammetry, spectrophotometry